Flot-2 Expression Correlates with EGFR Levels and Poor Prognosis in Surgically Resected Non-Small Cell Lung Cancer. - Qiuyuan Wen; Weiyuan Wang; Shuzhou Chu; Jiadi Luo; Lingjiao Chen; Guiyuan Xie; Lina Xu; Meirong Li; Songqing Fan (PLoS ONE, 2015)
We previously reported that expression of Flotillin 2 (Flot-2), a protein isolated from caveolae/lipid raft domains, increased significantly in nasopharyngeal carcinoma (NPC) compared with normal tissues. Signal transduction through epidermal growth factor receptors (EGFR) and Flot-2 play an important role in cancer development, but their precise role in lung cancer has not been investigated. In this study, we have investigated the correlation between the expression of Flot-2 and EGFR, which increase significantly in non-small cell lung cancer (NSCLC) patients (n=352) compared with non-cancer tissues. Additionally, patients with advanced stages of NSCLC had higher positive expression of Flot-2 and EGFR than patients with early stages. NSCLC patients with increased expression of Flot-2 and EGFR had significantly less overall survival rates than patients with less expression of Flot-2 and EGFR. Taken together, our data suggest that increased expression of Flot-2 and EGFR in NSCLC patients is inversely proportional to the disease prognosis and that increased expression of Flot-2 associated with increased EGFR may serve as a biomarker to predict poor disease prognosis.